The knowledge, attitudes and practices of soldiers in a gendarmerie command headquarters about family planning and venereal diseases - Oguzoncul, A. Ferdane; Deveci, S Erhan; Acik, Yasemin (SEAMEO TROPMED Network, 2011)
The objective of this study was to determine the knowledge, attitudes and practices of young male soldiers about family planning. This was a cross-sectional study conducted at the Gendarmerie Command Headquarters, Elazig City, eastern Turkey, carried out on 14 April 2004. One hundred ninety-one of 209 soldiers who were present at the Gendarmerie Command Headquarters were included in the study. A questionnaire, developed by the researchers evaluating the goals of the study, was filled out by the subjects prior to the Family Planning Seminar given to the soldiers. Data were assessed using SPSS and the chi-square test was used for statistical analysis. Defining family planning correctly, being familiar with planning methods and a knowledge of sexually transmitted diseases (STD) and their prevention was found to be at low levels among soldiers. A knowledge of family planning, birth control methods, identification and prevention of STD was higher with higher levels of education. The most familiar family planning methods were condom and oral contraceptive use. Soldiers constitute one of the most significant target groups for education programs.
Keywords: Contraception; Family planning; Gendarmerie; Venereal diseases